Colorectal cancer spectrum: From subtypes and epidemiology to oncotherapies - Nidhi Agrawal; S.K. Lanjhiyana; Meenakshi Jaiswal; Mohammad Akbar Siddiqui; Sakshi Gupta (Gastroenterology & Endoscopy)
Colorectal cancer (CRC) has an incidence rate of 10 ​% and is the third most common cause of mortality worldwide, following breast and lung cancer. The clinical symptoms of CRC appear in the last phases of the disease and there is a substantial golden period between the formation of polyps and the onset of cancer. There are many traditional options available for the treatment of CRC, such as surgery, chemotherapy, radiation therapy, etc. Although there have been significant advancements in conventional therapies, the management and prevention of CRC are still relatively challenging due to disease reoccurrence and resistance to chemotherapy. Recently, novel strategies including targeted therapy and immunotherapy have emerged as novel possibilities for treating CRC. The present article provides an overview of the molecular subtypes, epidemiology, carcinogenesis, risk factors, diagnostic approaches, and recent advancements in therapeutic options for the treatment of CRC.